Membrane Assembly and Ion Transport Ability of a Fluorinated Nanopore. - Raphaël Godbout (PLoS ONE, 2016)
A novel 21-residue peptide incorporating six fluorinated amino acids was prepared. It was designed to fold into an amphiphilic alpha helical structure of nanoscale length with one hydrophobic face and one fluorinated face. The formation of a fluorous interface serves as the main vector for the formation of a superstructure in a bilayer membrane. Fluorescence assays showed this ion channel's ability to facilitate the translocation of alkali metal ions through a phospholipid membrane, with selectivity for sodium ions. Computational studies showed that a tetramer structure is the most probable and stable supramolecular assembly for the active ion channel structure. The results illustrate the possibility of exploiting multiple Fδ-:M+ interactions for ion transport and using fluorous interfaces to create functional nanostructures.